STRATEGI HIDUP MASYARAKAT PETANI DI KELURAHAN PANDU, KECAMATAN BUNAKEN, KOTA MANADO - Reno Raven Derek; Elsje Pauline Manginsela; Benu Olfie L.S. (Sam Ratulangi University, 2016)
This study aims to describe how farmers carry out a strategy of life on three groups of farmer: upper layer, middle layer and peasant farmers to finance their family daily life. This research was conducted in the urban village of Pandu, Sub-District Bunaken, Manado City. Most of them live from farming activities. The research was conducted in November 2015 through to March 2016. The primary data obtained from interviews to three (3) groups. Selection of the sample is purposive stratified sampling. Each group selected five respondents, so a total of 15 respondents. Collection of secondary data derived from the Urban Village Office of Pandu, Manado City. The results showed that the upper and middle groups of farmers tend to apply the accumulation strategy while consolidation strategy was not found. The two groups have incomes that exceed the needs of farming and of the results they could buy a cow, land or other assets. While farmers lower group implement survival strategies. This farmersgroup use their earnings for the daily needs of the family and the other half to farm. Limited income makes farmers can not save even they have to borrow money to supplement the family income either eat or buy school supplies for children.